Design of an Executable Solutions Management Platform based on Virtual Machine Snapshots - Shoniwa, Robert; Fadaraliki, David; Catherine S, Monica; Marengereke, Tendai (My University, 2016)
Annually, dozens of software solutions are developed by students as part of the mandatory requirements for them to be awarded their respective degree qualifications. However, most of these potentially groundbreaking solutions tend to be stored away and forgotten upon completion. This then gives rise to the current predicament where universities produce multiple graduates but do not yield a proportional number of usable innovative software solutions. The aim of this paper is to design a platform that enables the storage, indexing, retrieval and execution of these developed solutions. This will be done through the design of a user-friendly interface as the front end, a database of virtual machine snapshots for each executable system running at the backend and a querying engine to interface the two. This will go far in ultimately aiding universities to become recognized hubs of innovative and marketable technologies.
Keywords: Solutions Management Platform; Virtual Machine Snapshots; Universities